সমাজ বিজ্ঞান, আমাদের অতীত দিনগুলো, অষ্টম শ্রেণির ইতিহাস - (:unkn) unknown (Tripura Board of Secondary Education, 2015)
This book is a History text book for Eight standard (Class VIII) of Tripura Board of Secondary Education.
Samaj Vigyan, Amader Otit Dingulo, History, Class-VIII
Keywords: Bengali; History; Bengali; Bengali